(untitled) (Andamios, Revista de Investigación Social, 2004)
This paper presents a general outlook on the mainstream orientations that prevail nowadays in Mexico City studies. These orientations fail to recognize the functioning of the city as a totality, operating on the basis of a serious fragmentation of the object under study. The author holds that the Distrito Federal is only a part of a real city, formed by the metropolitan zone of the Valle de México. Because of this, it is necessary to develop these kinds of studies in a metropolitan scale or, at least, pu- tting these fragmentary studies in a general context. The article also de- als with some fields of research that the strategist should take into account for the structural change of the metropoli.